La gestión ambiental en el sector público, aplicado a las competencias ambientales del GADMIC Pujilí, provincia de Cotopaxi. - Navarro Tapia, Wilson Javier (2023)
In the environmental management of the public sector there is poor planning and effective environmental policies and strategic actions to guarantee the care and protection of the environment. For this reason, the aim is to know the environmental management carried out in the public sector applied to the environmental competencies of the GADMIC Pujilí of the province of Cotopaxi. Starting from the identification of environmental problems, analyzing the regulations relevant to environmental management and evidencing the availability of GADMIC Pujilí resources, this through research using a qualitative and quantitative method using as a technique the interview directed to experts from the municipality and users, complemented with a network relationship analysis using the ATLAS Ti program. The result was the existence of progressive environmental management in the municipality since it works based on policies and programs focused on regulating, controlling and protecting environmental quality; In conclusion, there are problems with environmental sanitation, application of local environmental regulations, lack of infrastructure, equipment and technical personnel to comply with environmental management in the canton from the public sector.